Evaluation of the Implementation of SAK ETAP in Recording the Financial Reports of the Services Savings and Loan Cooperative - Mellinia, Salma Putri; Fadhila, Lulu Syifa; Rafinda, Ascaryan (Politeknik Ganesha Medan, 2025)
Jasa Savings and Loan Cooperative is a member-owned cooperative established in the 1970s by small and medium entrepreneurs. Its purpose is to help small and medium entrepreneurs get loans as business capital. IAI endorsed SAK ETAP on 19 May 2009. SAK-ETAP is a finance accounting requirement for organizations that lack societal accountability issued by IAI that is to be applied by certain entities when they present their financial reports. Services Savings and Loan Cooperative is one example of a cooperative that applies SAK ETAP to its financial reports. The goal of the study is to investigate how the use of Financial Accounting requirements for Organizations Without Social Accountability in the compilation of financial reports at Pekalongan Services Savings and Loan Cooperative. This is because SAK ETAP is likely to assist Pekalongan Services Savings and Loan Cooperative prepare better financial reports. The study methodology applied is a descriptive method with a qualitative technique. The informants in this study were the head and staff of the accounting and fiscal section and the membership section. The amount of informants in this research was six people. The data that is utilized is both primary and secondary. Primary data was collected within interviews, observations, and documentation. Secondary data are acquired from the literature studies that have to do with the research object by utilizing cooperative data in financial reports, theoretical supporting books, and the outcomes of prior research. The findings indicated that Pekalongan Services Savings and Loan Cooperative had implemented SAK ETAP properly and entirely in its financial reports.